Socialization of Building the Qur'ani Generation through Science and Technology Innovation and Creative Media in the Digitalization Era at Rumah Qur'an Madani - Kurniati Kurniati; Rahul Sabillilah; Zahid Irfani; Hari Wijaya; Muhammad Fatur Rahman; Muhammad Nurung (Talenta Publisher, 2025)
Rumah Quran Madani is located on Jalan Tanjung Bubuk, Bukit Baru, Ilir Barat 1, Palembang, in a densely populated area with many children. Although it has great potential as a Tahfidz Qur'an House, currently it only has 9 students, due to the lack of information and supporting media as well as outdated technology. To overcome this problem, we built a digital platform in the form of a website that is designed with an attractive and easy-to-use appearance. This website will display the full profile Rumah Qur'an Madani and detailed information on its programs, as well as facilitating the online registration process. In addition, this website will help in administrative management, by storing data and files neatly and structured, reducing manual record-keeping, and minimizing the risk of data loss. The attendance process will also be more efficient with the QR Code scanning feature, which stores attendance data directly in an online database, ensuring accurate and easily accessible information.